Effects of Social Media Marketing on Consumer Buying Behavior - Shrestha, Aditi; Karki, Alina; Bhushan, Mayank; Joshi, Shiwani; Gurung, Shreya (New Perspective: Journal of Business and Economics, 2023)
This study examines the effect of social media marketing on consumer buying behavior in Nepal, a typical developing country. The study used non-probability convenience sampling to survey 108 consumers and analyzed the effect of purchase intention, social network, social influence, and content marketing. Descriptive statistics, correlation, ANOVA, and multiple regression were employed for data analysis.The findings indicate that consumer buying behavior can be influenced by focusing on social network, social influence, and content marketing. The study aligns with previous research that highlights the importance of these factors in influencing consumer behavior. However, it is important to note that the literature review reveals a lack of research on the impact of social media on purchasing decisions in developing countries like Nepal. The implications of this study are significant for marketers in Nepal. Firstly, marketers should prioritize social media marketing strategies to influence consumer buying behavior. Secondly, they should pay attention to building strong social networks, leveraging social influence, and creating compelling content to engage consumers. Thirdly, marketers should consider the role of purchase intention in shaping consumer behavior. Lastly, developing effective social media marketing strategies is crucial for influencing consumer buying behavior. In conclusion, this study contributes to the understanding of the effect of social media marketing on consumer buying behavior in Nepal. The findings suggest that social media marketing can influence consumer behavior, and the identified factors of social network, social influence, and content marketing play a crucial role. The study highlights the need for further research in this area and provides valuable insights for marketers seeking to leverage social media to drive consumer engagement and purchasing decisions in developing countries like Nepal.